IDIOM DALAM BAHASA INGGRIS DAN BAHASA TOMBULU (SUATU ANALISIS KONTRASTIF) - Tumbel, Reiny Carolina; Pelealu, Hetty; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTÂ  Â  Â  Â  Â  Â  Â  This study entitled â€œIdioms in English and Tombulu Language (A Contrastive Analysis)â€. Idiom cannot be interpreted each word but must be interpreted as a whole by combining the meaning of each word or context of the conversation. This study focuses on idiomatic expressions in English and Tombulu Language. The aims of this research is to identify, classify and analyze the types and meaning of idiom in English and Tombulu Language, and to find out the similarities and differences of both languages. The writer used theory from Fernando (1996), Leech (1981) and contrasted the two languages using Ladoâ€™s (1975) concept. The results of this study shows that there are three types of idiom in Tombulu language, they are: Pure idioms, semi-idioms and literal idioms. It also shows that the two languages have similarities and differences.Keywords Idiom: Types and meaning, contrastive analysis, English and Tombulu Language